Determinants of vitamin A status among pregnant women participating in the Mama SASHA Cohort Study of Vitamin A in Western Kenya: preliminary findings. - Akelo, V.; Grant, F.; Okuku, H.S.; Wanjala, R.; Low, Jan W.; Cole, D.; Levin, C.; Girard, Amy W. (2014)
Mothers’ vitamin A (VA) status during pregnancy and lactation determine infants’ VA levels. We estimated VA status during pregnancy and assessed its determinants using data on 505 pregnant women attending first antenatal care visit in Western Kenya. VA and iron status were assessed using plasma retinol binding protein (RBP), and ferritin and transferrin receptor, respectively, corrected for inflammation as measured by C-reactive protein (CRP>5 mg/L) and α-1-acid glycoprotein (>1 g/L)]. Anemia was assessed with Hemocue hemoglobinometer. Only 34% of women had heard of VA, and 26% of them could not specify its importance. School was the most common source of VA information (68%), followed by health facility (19%). Mean (±SD) RBP was 1.44 (±0.35) µmol/l and the prevalence of VA deficiency (VAD) was 21.8%. Prevalence of inflammation (by CRP) was 24%. Anemia, but not iron deficiency anemia, was the only factor associated with VAD (OR (CI): 1.68 (1.05, 2.71). Other potentially modifiable factors, including food insecurity, dietary diversity, awareness of VA, household or maternal consumption of VA rich foods, maternal MUAC and gestational age were not associated with VAD. The prevalence of VAD is high among pregnant women in Western Kenya and associated with anemia but not iron deficiency anemia. Additional research is needed to understand the etiology of VAD in this population.